Rhodanine-based dyes absorbing in the entire visible spectrum. Issue 6 (21st February 2017) - Sandoval-Torrientes, Rafael; Calbo, Joaquín; García-Fresnadillo, David; Santos, José; Ortí, Enrique; Martín, Nazario
Abstract : A series of new broad-absorbing rhodanine-fluorene dyes conjugated with triarylamines are presented. Spectroscopic and electrochemical characterizations, along with theoretical DFT calculations, unveil the electronic and optical properties of the dyes. Abstract : A series of new broad-absorbing dyes based on rhodanine derivatives conjugated with triarylamines using a fluorene backbone was synthesized. Spectroscopic and electrochemical studies, along with density functional theory (DFT) calculations, provided clear insight into the electronic and optical properties of the dyes, which efficiently absorb in the entire visible spectrum.